Attenuation of Retinal Endothelial Vasodilator Function in a Rat Model of Retinopathy of Prematurity. (2nd December 2019) - Nakano, Ayuki; Mori, Asami; Arima, Shiho; Asano, Daiki; Morita, Akane; Sakamoto, Kenji; Nagamitsu, Tohru; Nakahara, Tsutomu
ABSTRACT: Purpose : Retinopathy of prematurity (ROP) is characterized by morphological abnormalities in retinal blood vessels, but how an episode of ROP affects vascular function remains to be fully elucidated. The purpose of the present study was to assess the distribution of pericyte/smooth muscle in retinal blood vessels and retinal vasodilator responses in a rat model of ROP. Methods : ROP was induced in rats by the subcutaneous injection of the vascular endothelial growth factor (VEGF) receptor tyrosine kinase inhibitor KRN633 (10 mg/kg) on postnatal day (P) 7 and P8. The distribution of pericyte/smooth muscle in retinal blood vessels was examined on P14 and P35 by immunohistochemistry. Retinal vasodilator responses were assessed on P35 by measuring the diameter of retinal arterioles in fundus images. Results : In retinas of KRN633-treated (ROP) rats, progressive angiogenesis, tortuous arteries, enlarged veins, and enhanced expression of α-smooth muscle actin in pericytes on capillaries and veins were observed on P14. These abnormalities in retinal vasculature showed a tendency to normalize by P35. Vasodilation of retinal arterioles induced by acetylcholine, an endothelium-dependent vasodilator, was smaller in P35 ROP rats than age-matched controls, whereas retinal vasodilator responses to the nitric oxide (NO) donor NOR3 were unaltered. Conclusions : Phenotypic changes in pericytes occur in the ROP model rats and endothelium-dependent vasodilatory mechanisms in retinal blood vessels are impaired. The impaired vasodilator function may contribute to the progression and pathogenesis of ROP.